CHILD’S SELF-CONCEPT FORMATION IN CONDITIONS OF INFORMAL EDUCATION (CROSS-CULTURAL ASPECT) - Kolodych, Daria (PSYCHOLOGICAL JOURNAL, 2019)
The following scientists were engaged in research on the dynamics of the self-concept in childhood – Huitt W., James W., Rogers С., Robert B. Burns. They believe that the development of self-concept is a process of gaining knowledge about yourself, awareness of yourself as an active subject of life. The child gradually builds a cognitive theory about who he is and what he is capable of, and uses it in adapting his behavior. At school age, self-esteem also depends on self-confidence in learning. Children who have good academic performance usually have high self-esteem, while children with low academic performance have correspondingly low self-esteem. But it should be noted that self-esteem is strongly socially determined. So we decided to investigate the influence of cultural factors on the development of children's self-concept in the conditions of informal education. The study involved 25 Ukrainian and 18 Vietnamese students (this is their total number in this educational program). The children ranged in age from 7 to 12 years. We used the following methods - “Self-assessment of Dembo-Rubinstein” Kuhn – McPartland test “Who am I?” and projective image “I’m on English language courses”. Classes at courses in Ukraine took place in small groups, 4-8 people in each, and in Vietnam as well. In addition to learning the English language courses, all students attending secondary schools in their cities. Significant differences were identified according to the Mana-Whitney criterion (at the level of 0.05) according to the competency scales (“Ability to draw” and “Ability to speak English”) and on the “Level of happiness” scale. Indicators of individual characteristics, such as “Beauty”, “Mind”, “Kindness” do not have significant differences. It is likely that the greater personal involvement of Ukrainian children in informal education and the subjective importance of the skills acquired during the study in sections has a positive effect on the childrens’ assessment of their skills. Despite the fact that the Ukrainian children positively evaluate their skills, they are generally lower rate their individual characteristics and level of happiness.